Socialization of Tax Procedure for Domestic Taxpayers Receiving Income Abroad in Pulau Pinang Malaysia - Tarmidi, Deden; Setiany, Erna; Bin Rahmad, Khozaeni; Ali, Anees Janee (EQUATOR SINAR AKADEMIA, 2024)
In the era of the global economy, cross-border business activities are widespread, including the urbanisation of citizens abroad, one of which is a member of the Pertubuhan Masyarakat Indonesia (PERMAI) on Penang Island Malaysia both as expatriates, students, entrepreneurs and as a workforce in Malaysia which has an impact on increasing foreign exchange earnings. Specifically, through the Minister of Finance Regulation Number 18 of 2021, the Government of Indonesia has provided direction on how to manage the tax status for domestic taxpayers who work and earn income abroad, or vice versa. However, many taxpayers do not understand their tax status when working and earning income abroad and have the wrong perception that they are at risk of getting a tax bill from the tax authorities in Indonesia, so socialization is needed. This community service activity aims to provide education about tax procedures for Indonesian taxpayers who work and earn income abroad and provide assistance in carrying out procedures according to applicable regulations. This activity was held in Pulau Pinang Malaysia in January 2024 to 75 Indonesians who are domiciled and have income abroad. With the socialization and question and answer method, it was found that all participants did not know the rules and did not understand how the procedure should be before the activity took place. The understanding of the participants increased after the activity, and the majority of participants became vigilant and intended to coordinate with their families in Indonesia regarding their Tax ID Numbers.